2015
DOI: 10.15517/rbt.v58i1.20025
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term coral-algal dynamics and conservation status of a Gorgona Island (Tropical Eastern Pacific) coral reef

Abstract: <span>A través del Sistema Nacional de Monitoreo de Arrecifes Coralinos en Colombia (SIMAC) se han colectado anualmente (1998-2004) datos de cobertura de corales y algas en 20 transectos de 10m localizados en dos profundidades de dos sitios del arrecife de La Azufrada, Isla Gorgona (costa Pacífica). En general, la cobertura coralina fue alta (55.1% - 65.7%) y la de algas baja (28.8% - 37.5%), con una significativa variación entre años, más notablemente en áreas someras. Las diferencias entre sitios tanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
4
17
0
1
Order By: Relevance
“…This study extends the results of a previous study (Zapata, et al, 2010) on the benthic dynamics of La Azufrada coral reef that spanned the first seven years (1998)(1999)(2000)(2001)(2002)(2003)(2004) of the period considered here. The larger duration of the current study allows a more detailed evaluation of the observed dynamics and its potential drivers in the light of hypotheses previously proposed (Zapata, et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study extends the results of a previous study (Zapata, et al, 2010) on the benthic dynamics of La Azufrada coral reef that spanned the first seven years (1998)(1999)(2000)(2001)(2002)(2003)(2004) of the period considered here. The larger duration of the current study allows a more detailed evaluation of the observed dynamics and its potential drivers in the light of hypotheses previously proposed (Zapata, et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…The larger duration of the current study allows a more detailed evaluation of the observed dynamics and its potential drivers in the light of hypotheses previously proposed (Zapata, et al, 2010). A major (~27.5%) decline in coral cover was observed over the first decade (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) of the study, causing concern that coral reefs of Gorgona Island were exhibiting a decline like that observed in many coral reefs worldwide (Gardner, et However, the recovering trend observed since 2009 and the lack of major changes in environmental conditions around La Azufrada coral reef during the time of the study suggest that changes in coral cover are not simply the result of deteriorating conditions caused by local anthropogenic impacts.…”
Section: Discussionmentioning
confidence: 91%
“…The maximum densities were higher than most Caribbean octocoral communities (Sánchez et al, 2005;Etnoyer et al, 2010), whereas the number of species per site is slightly lower in Gorgona Island. A notable difference with Caribbean octocoral communities is that TEP assemblages do not coexist with branching reef-building corals, e.g., Pocillopora spp., which form dense coraldominated areas in Gorgona Island (Zapata et al, 2010). Similar octocoral densities have been observed in the oceanic island of Malpelo in a community dominated by only two seafan species together with L. alba (Sánchez et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…1). The scleractinian corals of Gorgona island have been studied in detail, given that the leeward side of the island includes one of the few well-developed coral reefs of the TEP (Zapata, Rodríguez-Ramírez, Caro-Zambrano & Garzón-Ferreira, 2010). In contrast, octocorals in Gorgona island have not been studied except for a few records of species in a taxonomic account of the Colombian Pacific (Prahl, Escobar & Molina, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…The fringing coral reefs on the eastern side of the island provide habitat and resources for a variety of organisms, including fish, echinoderms, polychaetes, mollusks, crustaceans, bryozoans, hydroids, sponges and algae, among others (Barrios-Suárez & López Victoria, 2001;Acevedo-Bueno, Beltrán-León & CaicedoTulante, 2004;Zapata, Rodríguez-Ramírez, Caro-Zambrano & Garzón-Ferreira, 2010). The pelagic zone also offers food resources, with 136 species of phytoplankton (75% diatoms and 23% dinoflagellates in October; 69% diatoms and 30% dinoflagellates in March), and 96 zooplankton families having been reported (Soto et al 2001;Giraldo et al, 2011;Giraldo, Valencia, Acevedo & Rivera, 2013).…”
Section: Study Areamentioning
confidence: 99%